Relation between coaching behavior and role ambiguity - Karamousalidis, G.; Galazoulas, C.; Manousaridou, E.; Bebetsos, E.; Grammatikopoulou, M.; Alexaki, A. (Journal of Physical Education and Sport, 2010)
The purpose of this research was to investigate the relationship between coaching behavior and role ambiguity in defensive responsibilities using interdependent Greek sport teams. Athlete perceptions of role ambiguity (defense) were assessed using a questionnaire developed by Beauchamp, Bray, Eys and Carron (2002) and coaching behavior was assessed using the Coaching Behavior Questionnaire, (Williams, et. al., 2003). The sample consisted of 409 athletes of basketball, volleyball, handball and soccer. Confirmatory factor analysis provided the construct validity of the questionnaires and correlations among the scales confirmed construct validity. The implications of the results are discussed and future research should continue to investigate the multidimensional models of both coaching behavior and role ambiguity in sport settings.